Easy Sdn Bhd: push up bottle / Nurul Hezaty Mohamad Adnan … [et al.] - Mohamad Adnan, Nurul Hezaty; Nik Abdullah, Nik Hanis Suhaili; Mohd Khalid, Nurhazirah Hanani; Syamsul Kahar, Muhammad Arif Hakimy (2022)
Our company, Easy Sdn Bhd is a Private Limited Company (Sdn Bhd) located at 65, Jalan Eco 1, Zone Industry Ayer Keroh Baru, Hang Tuah Jaya, 75450 Melaka, Malaysia. Since 1st May 2022, we started our business by joining the Original Equipment Manufacturer (OEM) as a new firm in the Food & Snack packaging industry. Nurul Hezaty Binti Mohammad Adnan have been appointed as the Chief Executive Officer (CEO) of our company, alongside with the other top management position which are general manager, marketing manager, logistic manager, and financial manager. As a new company in this industry, Easy Sdn Bhd mission is to improve the food packaging, specifically snacks, by providing a high quality components materials, which added values to our customers’ branding and provide the consumers with a new life-changing experience of “snacking time”. In accordance with the company mission, our main product and services is “Push –Up Bottle”. It is a versatile packaging material which is made out of rigid paperboard and aluminium containers that help prevent delicate foods like chips from crushing. Our packaging are focusing on the ability to store fragile foods with additional upward mechanism, which is to ease the consumers when they are consuming the snack. Other than that, this container will enable the consumer to organise their food better at home and this container is also travel friendly. Through segmentation market, our client or target market is the food manufacturers. To attract this potential client, we produce a low-cost packaging with a lot of benefits in terms of its durability and its practicality in consuming their products. With the current market, we will hold 30% market share among our competitors in the food packaging industry. We are able to achieve a big market share due to the uniqueness of our product, which is with its high quality and futuristic design. One of the major attraction is the upward mechanism feature in our packaging that no other competitors has ever built. Therefore, holding the second highest position of the market share in this industry shows that we have won the heart of our user. Last but not least, financial aspects needs to be taken seriously and considered as a major part of the business. In determining financial projections, there are several procedures need to be done, such as preparation of the total project cost and choices of financial sources. Easy Sdn Bhd first year sales projection is RM5,560,000 and the production cost projection is RM401,791. As for the second year, the sales projection increase to RM6,522,320 and the production cost projection has decrease to RM396,806. As for the third year, the sales is projected to be RM7,050,000 and RM396,326 is projected for the production cost. Overall, we believe our business will thrive more in the future with a bigger numbers and it will also benefits us and our consumers.